2017
DOI: 10.18410/jebmh/2017/41
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Attitude of Puerperal Women Towards Family Planning Practices in a Tertiary Care Hospital

Abstract: BACKGROUNDIndia is the second most populous country in the world after China. In an effort to stabilize the population, National Family Welfare Program was launched in 1951. There has been an increase in contraceptive prevalence and a reduction in total fertility rate since then. For better results, contraceptive use should start right from the post partum period. This also significantly reduces maternal and infant mortality rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
2
2
Order By: Relevance
“…2,3,6,7 Nair et al, Deka et al and Bhargava et al found that the knowledge was 80%. [8][9][10] However, the awareness in our study was higher than the study done by Malik et al where only 68.4% were aware of contraceptive methods. 11 It was found that 64.3% of our women had knowledge about permanent methods of sterilization which was comparable to a study done by Lakshmi et al in Tirupati where 58% had knowledge.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…2,3,6,7 Nair et al, Deka et al and Bhargava et al found that the knowledge was 80%. [8][9][10] However, the awareness in our study was higher than the study done by Malik et al where only 68.4% were aware of contraceptive methods. 11 It was found that 64.3% of our women had knowledge about permanent methods of sterilization which was comparable to a study done by Lakshmi et al in Tirupati where 58% had knowledge.…”
Section: Discussioncontrasting
confidence: 79%
“…[11][12][13] The main source of knowledge about permanent method of sterilization in our study was found to be from health care professionals mainly doctors and nurses as stated in similar studies in comparison with other studies where knowledge was updated mainly through newspapers and mass media. 1,2,6,[8][9][10] According to Lakshmi et al most women preferred to undergo permanent sterilization procedure after having 2 to 3 children 3 whereas in our study 5.6% of women wanted to have 4 children and 1% even expressed her desire to have more than 4. Most of the women in a study done by Malik et al in Pakistan had parity more than 5.…”
Section: Discussionmentioning
confidence: 53%
“…In .1% belonged to 25-34-year age-group. 9,10 Majority in our study were uniparous (48.6%) while it was 32 % and 43.3% in the studies by Thapa Majority (59.4%) of our study population were Hindus, 28.3% Muslims and 12.1% Christians whereas in the study by Nair A et al, 42% were Hindus, 56% Muslims and 2% were Christians.…”
Section: Discussioncontrasting
confidence: 59%
“…Many factors affecting the use of contraceptive methods in the sub-Sahara African context have been observed. Many of them repeatedly cited women’s level of education and place of residence as major determinants of contraceptive use ( Fawole & Adeoye, 2015; Nair & Devi, 2017; Ochako et al , 2017). Most of these studies have examined the separated effect of the place of residence and education on contraceptive use.…”
Section: Introductionmentioning
confidence: 99%